2021
DOI: 10.52690/jswse.v1i3.112
|View full text |Cite
|
Sign up to set email alerts
|

Visionary Leadership and Organizational Culture on Teacher’s Performance

Abstract: This study determined the effect of Visionary Leadership and orgazitional culture on the performance of Vocational High School Teacher in Prabumulih City. This research uses quentitative approach with Survey Method. This study population of 125 people, namely vocational High School teacher in Prabumulih city. The research sample of 30 people. The sampling technique in this study is random sampling. Data collectional technique using documentational and questionnaire. Data were analyzed using simple regression t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…The failure of an organisation is caused by a leader because he or she cannot formulate his or her vision into the mission of his or her organisation, and most organisations are not responsible for the vision and mission made by the leader of the organisation. This is supported by the results of previous research, namely Kurniadi, Lian and Wahidu (2020), suggesting that Islamic visionary leadership has a positive and significant effect on employee performance. Furthermore, research by Miharja and Hayati (2021) stated that Islamic visionary leadership has a positive and significant effect on employee performance.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…The failure of an organisation is caused by a leader because he or she cannot formulate his or her vision into the mission of his or her organisation, and most organisations are not responsible for the vision and mission made by the leader of the organisation. This is supported by the results of previous research, namely Kurniadi, Lian and Wahidu (2020), suggesting that Islamic visionary leadership has a positive and significant effect on employee performance. Furthermore, research by Miharja and Hayati (2021) stated that Islamic visionary leadership has a positive and significant effect on employee performance.…”
Section: Introductionsupporting
confidence: 85%
“…Likewise, Syarif and Lina (2019) stated in their research that Islamic visionary leadership has a positive and significant impact on employee commitment to the organisation. Kurniadi et al (2020) suggested that Islamic visionary leadership has a positive and significant effect on employee performance. Research by Miharja and Hayati (2021) Hendri ( 2019) in his research stated that organisational commitment has a positive and significant effect on employee performance.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The t distribution table shows that the t table value (t, df: n-2) = (t 0.05, 18) = 2,100. The calculation above shows that t count > t table (2.610 > 2.100), implying that managerial supervision has a significant effect on the principal's performance (Kurniadi et al, 2021).…”
Section: The Effect Of Managerial Supervision On the Performance Of T...mentioning
confidence: 88%
“…Then determine how much influence the independent variables have on the dependent variable when they are combined. This analysis was carried out using the SPSS program, and the following summary table was Based on the description of the simple analysis above, it is possible to conclude that organizational culture and performance motivation variables have a positive and significant influence on employee performance (Prihatini et al, 2021;Kurniadi et al, 2021;Maryati et al, 2020).…”
Section: Journal Of Social Work and Science Educationmentioning
confidence: 99%